Experience of Cryptocurrency Legal Regulation: Comparative Legal Analysis - Wojciech Słomski (Communications of International Proceedings, 2022)
The article discusses the international experience of cryptocurrency regulation since the beginning of their widespread use on the example of the United Kingdom, the United States, Australia, Ukraine, Japan, China and Latin America countries. Most of the countries, such as the United States, Australia, EU countries, as well as such financial and technological giants as China and Japan are positive-expectant concerning the status of cryptocurrencies. The neutral position of a number of countries (the European Union, Latin American countries) is due to the lack of developed legislation regulating cryptocurrency relations.
Keywords: cryptocurrency; money surrogate; international legal regulation; bitcoin; blockchain; cryptocurrency exchange; taxation; digital currency.